2010
DOI: 10.1249/01.mss.0000384790.02567.c0
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Verbal Encouragement and Wingate Anaerobic Cycle Test Performance in Females: Athletes vs. Non-Athletes

Abstract: To examine the effect of concurrent verbal encouragement on the performance of the WAnT in female athletes vs. female non-athletes. College-age female subjects were recruited where ten of the subjects were intercollegiate athletes (ATH, n1=10) and the nine were non-athletes (NON, n2=9). The WAnT was novel to all subjects and the subjects were blinded to the study’s purpose. Prior to the experimental trials, subjects were measured for body composition and performed a familiarity WAnT trial without verbal encour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 9 publications
0
8
1
1
Order By: Relevance
“…However, only conclusions comparing preferred to non-preferred music can be made using the current data set, leaving how these conditions compare to no music unknown. Lastly, it is customary to give participants verbal encouragement during WAnTs as it has been shown to positively affect performance [32]. Given that participants were focusing on the music they were listening to rather than verbal encouragement, our results may not be comparable to previous investigations utilizing verbal encouragement.…”
Section: Discussioncontrasting
confidence: 57%
“…However, only conclusions comparing preferred to non-preferred music can be made using the current data set, leaving how these conditions compare to no music unknown. Lastly, it is customary to give participants verbal encouragement during WAnTs as it has been shown to positively affect performance [32]. Given that participants were focusing on the music they were listening to rather than verbal encouragement, our results may not be comparable to previous investigations utilizing verbal encouragement.…”
Section: Discussioncontrasting
confidence: 57%
“…Consequently, studies investigating the effect of VE on endurance performance using different tests and encouragement settings revealed inconsistent findings. On one hand, recent studies reported no significant effect of VE on performance during Wingate anaerobic test between female athletes and non-athletes (Bullinger et al, 2012). Additionally, duration of the Wingate anaerobic Test is only 30 s. Therefore, an encouragement frequency of 60 s is not possible and findings of longer lasting test efforts are difficult to compare to.…”
Section: Discussionmentioning
confidence: 96%
“…Only one study examining the efficacy of verbal encouragement during maximal exercise test performance has specified exactly what was said as part of the encouragement, by referring the reader to the guidelines for the 6-min walk test (Marinho et al, 2014). Other studies provided examples (Guyatt et al, 1984;Andreacci et al, 2002;Bullinger et al, 2012;Neto et al, 2015), or no description (Moffatt et al, 1994;Chitwood et al, 1997) of the encouraging words or phrases. So that future research can compare the relative efficacy of different content, tone, loudness, timing and frequency of verbal encouragement, we also recommend that such research describes details of the encouragement in full.…”
Section: Psychological Basismentioning
confidence: 99%